The construction and occupation of the Agro-village Leonardo D’Vinci in the Transamazon, in the 1970s (PerCursos, 2022)
The construction of the Transamazon Highway, in 1970, projected the transference of populations, especially from the Northeast and South regions of Brazil, to the population centers that would be implemented on its margins. From dialogues with residents, as well as analysis of news in newspapers with national circulation, it is evident that the Agro-village Leonardo D’Vinci it constituted a population nucleus whose history brings important social dynamics to understand the colonization program and the challenges that brought the lives of people who believed in the government's call and left for the Amazon. The trajectory of agro-village brings the dilemmas of the colonization program implemented by the Transamazon, which ignored the local populations and brought problems for them and for the migrants who left for the highway, in search of a better life.
Keywords: agro-villages; Transamazon; dictatorship; Amazon